2005
DOI: 10.1116/1.1849219
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective low-damage processes using advanced neutral beams for porous low-k films

Abstract: Etch induced sidewall damage evaluation in porous low-k methyl silsesquioxane films J. Vac. Sci. Technol. A 25, 986 (2007); 10.1116/1.2717192 In situ real-time monitoring of profile evolution during plasma etching of mesoporous low-dielectric-constant SiO 2 A highly selective and low-damage damascene process for porous methyl-silsesquioxane ͑porous MSQ, k-2.2͒ films has been realized using a neutral beam system we have developed. Use of a SF 6 or CF 4 neutral beam enables etching of porous MSQ with higher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…[6][7][8][9][10][11][12] To make NBE practical on an industrial scale, the energy and flux of the fast neutrals need to be comparable to those of ions in reactive ion etching. To obtain a high flux of fast neutrals, Panda et al 13 and Samukawa et al [14][15][16] have used high density inductively coupled plasmas ͑ICP͒. Ions were expelled from the plasma through a grid with high aspect ratio holes.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] To make NBE practical on an industrial scale, the energy and flux of the fast neutrals need to be comparable to those of ions in reactive ion etching. To obtain a high flux of fast neutrals, Panda et al 13 and Samukawa et al [14][15][16] have used high density inductively coupled plasmas ͑ICP͒. Ions were expelled from the plasma through a grid with high aspect ratio holes.…”
Section: Introductionmentioning
confidence: 99%
“…The next section focuses on highly efficient neutral beam generation using negative ions in a pulse-timemodulated plasma. 22) We found that high-flux low-energy neutral beams could be generated by efficiently neutralizing negative ions in a pulsed ICP passing through a carbon plate having high-aspect-ratio apertures. This system radiates very few charged particles or UV photons as a result of creating a partition between the plasma and the sample using a carbon plate.…”
Section: Problems In Conventional Plasma Etching Processesmentioning
confidence: 99%
“…There are two types of HNB source configurations: an ion source with an assembly of neutralization plates 5 and a plasma source with neutralization grids. 6,7 In case of the first type, it is difficult to generate a high flux HNB due to the space charge limited ion current extracted from the ion sources. The HNB sources of the second type have a capability to generate a high flux HNB but the scale-up is limited due to the difficulty of cooling the neutralization grids which consist of hole arrays.…”
Section: Introductionmentioning
confidence: 99%